Factors Influencing the Quality of FamilyBased Care among Older Adults in Nigeria - Obiyo, Ngozi; Christy , N. Obikeguna (International Journal of Psychosocial Rehabilitation, 2021)
The nature of older adults necessitated that they receive quality care. Some of them may have some physical impairments or motor disabilities, which will require them to need help and care. The present study investigated the factors influencing the quality of family based care among older adults in Delta State, Nigeria. Cross-sectional survey design was adopted for the study. The respondents were 1107 older adults. 12 respondents (comprising of 2older adults and 2 caregivers) was selected from each of the 3 Local Government Areas(LGAs) for In-depth interview [IDI]. Forty-eight respondents made up of 24 caregivers and 24 older adults were purposively selected for Focus Group Discussion [FGD], from the three LGAs. This implies 16 (8 caregivers and 8 older adults from each LGA. Thus, the total sample size for the study was 1167 respondents. Majority (72.7%) of the respondents indicated that it was cultural to take care of older adults within the family. Distribution along lines of place of residence revealed that 71.5% were urban residents, 68.8% were semi-urban residents and 77.6% were rural residents. Out of the respondents who indicated that it cost them exorbitantly to take care of older adults, 47.0% were lower income earners while 24.8% were higher income earners. It is cultural to take care of older adults and this is because at a point in time when the caregiver was young the now older adult was the career of the younger person. Place of residence studied were urban and rural dwellers. Some of the older adults were on pension. The study has proved that Family Based Care for older adults has prospects in Ndokwa area of Delta Stat, Nigeria. It was recommended that Local government authorities should provide remuneration and incentives for caregivers and care receivers irrespective of residence.